Caracterización sociodemográfica y clínica de los pacientes atendidos en la unidad de salud mental de la E.S.E. Hospital Pio XII Colon Putumayo - Rosero Villota, Nora Elena; Cerón Souza, Cristina (Universidad y Salud, 2007)
Introduction: after two years of the inauguration of first unit of mental health in the department of Putumayo was necessary to have an objective knowlege, sociodemographic and clinic of the attended population. Materials and Methods: Descriptive retrospective research. The research included the total of ambulatory population (one year) of hospitaizad patients (two years). Results: the mental desease affect with more frequency to maculine population, ratio of 1.4 and 1.5 in hospitalization and ambulatory population respective. The most frequent diagnosis in hospitalization was paranoid esquizofrenia (20.8%) and bipolar disrider (17.5%) and in ambulatory population was depressive adaptative disorder. The army conflict and the yagé consumption were the environmetal factors in the two populations. Coclusions: The results were agreed with the literature. There are differences among the tested populations. The mental disease produces a big deterioration in the global performance. Recomendations: Research of most evidence is necessary for to prove the hypothesis.